Conceptual framework of Islamic banking & finance: An alternative approach based on existing models - Htay, Sheila Nu Nu; Abdul Aziz, Muhammad Zahid; Hamat, Mustapha (2011)
Islamic banking industry is tremendously growing worldwide and no exception in the case of Malaysia. Malaysian Government is very supportive for the development of the Islamic banking and to ensure that Malaysia will become the center and the heart of the Islamic banking and finance. Even though, the rapid growth of the Islamic banking in Malaysia, it has been criticized for fulfilling or discharging the responsibility of Islamic institutions. A few researchers such as Halim and Chapra have come out the Islamic banking models. However, in the researchers’ opinion, these models need to be modified after considering the current Islamic banking practices and so far, no research has been done on it. Therefore, the purpose of this research is to propose the alternative conceptual framework on which true Islamic banking should be founded. It is believed that this research will provide a foundation to further research in Islamic banking and finance.